Systemic proinflammation after Mycobacterium tuberculosis infection was correlated to the gut microbiome in HIV‐uninfected humans. (15th March 2019) - Huang, Shiang‐Fen; Yang, Ying‐Ying; Chou, Kun‐Ta; Fung, Chang‐Phone; Wang, Fu‐Der; Su, Wei‐Juin
Abstract: Background: The dysbiosis of gut microbiome and interaction with host immunity after Mycobacterium tuberculosis (MTB) infection are under investigation. We had found fatigue symptom concurrent with dysbiosis by decreasing the ratio of Firmicutes to Bacteroidetes (F/B ratio) in active tuberculosis (TB). The study aims to assess the inflammatory biomarkers and their interaction with gut microbiome in active TB and latent TB infection before starting anti‐TB regimens. Materials and method: Interleukin‐1 beta (IL‐1B), IL‐4, IL‐6, IL‐10, CD3+, CD4+, CD8+ T cells and interferon‐gamma (IFN‐γ) releasing assay (IGRA) were measured in 25 active TB patients, 32 LTBI subjects and 23 healthy controls (HC). Gut microbiome profiles were obtained using 16S rRNA MiSeq sequencing method. Results: The leucocytosis (7032 ± 387 cell/cum, P  < 0.05), increase in IL‐6 (229.7 ± 104 µg/dL, P  < 0.05), and decrease in IL‐4 (0.27 µg/dL ± 0.1, P  < 0.05) were presented in active TB. The proportion of polymorphic neutrophil (PMN) in peripheral blood was positively related to the relative abundance of Bacteroidetes in LTBI and active TB ( R 2  = 0.23, P  < 0.05). The F/B ratio was positively related to the detectable IL‐1B in TB ( R 2  = 0.97, P  < 0.01) and to the IL‐4 in LTBI ( R 2  = 0.27, P  < 0.05). In LTBI, the relative abundances of Coriobacteriaceae were positively related to the secretion of IFN‐gamma against MTB‐antigens more likely associated with of CD4+ T cell ( R 2  = 0.42, P  < 0.05). Conclusion: In active TB, dysbiosis with higher relative abundances of Bacteroidetes in stool and low F/B ratio was related to systemic proinflammation. In LTBI, dose‐response relationship between peripheral PMN and relative abundances of Bacteroidetes was remained but not leads to systemic inflammation.